Christiane Rochefort et Le Repos du guerrier : le scandale de la jouissance féminine - Willem Hardouin-Zanardi (Genre, Sexualité et Société)
This article focuses on the first novel of Christiane Rochefort, Warrior’s rest, starting from the criticism which was contemporary with its release: its sexual subject. If, in 1958, this novel could appear shocking, it was not so much because of its vocabulary, as critics tried to make believe, but above all because of how words are used: Rochefort is specifically interested in female pleasure. This is not just a means of provocation. In the 1960s, sex is a political issue: the power issues of the novel are thus questioned. Moreover, the feminist message is clearly highlighted, both in its originality and in its universality. By freeing from patriarchal myths, Rochefort’s writing not only demonstrates that female pleasure exists, but also that it goes beyond scandal to reorganize society.